The Effect of Tabata Exercises on Muscular Strength and Muscular Endurance in Children Aged 13-14 who Received Taekwondo Training - Neslihan Akçay; Merve Çoban; Melike Nur Akgül; Mahmut Esat Uzun; Mustafa Şakir Akgül (ümit doğan üstün, 2021)
As in most branches, being fast, strong and strong is a prerequisite for a good performance in taekwondo. Again, many different opinions are put forward for the improvement of strength performance in children. In this context, this study investigated the effect of tabata exercise, which is one of the high intensity interval training methods, which is frequently reported to have positive effects on aerobic, anaerobic and strength performance in both adults and children. Thirty children (age 14.3 ± 0.21 years, height 159.1 ± 2.04 cm, body weight 50.9 ± 2.11 kg) who received Taekwondo training voluntarily participated in the study. Later, the participants were randomly divided into two groups as the Tabata group (n: 15) and the control group (n: 15). In addition to their routine taekwondo training, the Tabata group was trained with exercise sets determined 3 days a week for 8 weeks (3x4 movement in the first week, 20 seconds rest 20 seconds in the following weeks by increasing one movement). The control group, on the other hand, participated in their own routine taekwondo training 3 days a week for 8 weeks. Vertical jumping, standing long jump, medicine ball throwing, sit up and push-up tests were applied to all participants at the beginning, 4th week and at the end of the study. SPSS 23 package program was used in the analysis of the data. The test results of the research group at the 1st, 4th and 8th weeks were used with the Repeated Measures ANOVA Test to determine from which group the difference was caused by the Bonferroni test. Statistical significance level was accepted as p <0.05. In the study, when the evaluation was made within the group, a significant difference was found in the vertical jump, medicine ball throwing and sit up tests in the tabata group. In the control group, a significant difference was found only in the sit up test. When comparing between groups, there was no significant difference in all parameters between the two groups. Exercise can be said to have a positive effect on strength performance in children aged 13-14 who received taekwondo training.